Pearl pin inhalation accidents: an emerging tracheobronchial challenge to surgeons - Dar, Nisar Hussain; Dar, Khurshid Ahmad; Qadir, Waseem; Ain, Qurat Ul; Yousuf, Aamir (International Journal of Research in Medical Sciences, 2017)
Background: The practice of wearing head scarf pin or pearl pins is very common among young Muslim girls and wrong habit of holding a number of pins in the mouth and utilize them one by one to fix the scarf leading to accidental inhalation has emerged a frequently seen entity in our practice now and managing the tracheobronchial pearl pin foreign body poses a lot more different challenges to surgeon than conventional foreign bodies. The study presented an experience with pearl pin inhalation and discussed the unique clinical characteristics of this problem and challenges in management. Methods: A cross sectional hospital based observational study was conducted in tertiary care hospital (SMHS), department of ENT for period of 2 years August 2013 to July 2015. Results: Total of 36 (34 females and 2 males) patient were considered with mean age of 14.2 years (range 6-32 years). The average duration of reporting to our emergency department was 5 hours with delayed presentation ranging from 24 to 36 hours. In 31 patients the pin was successfully removed with rigid bronchoscope and in 2 cases fibreoptic bronchoscopy was needed, thorocotomy for more distal location was done successfully in two cases and another one gastroenterologist consultation was sought for reverse ingestion in to the abdomen. Conclusions: Pearl pins behave as floating or/are mobile in nature especially in the early phase of inhalation and initial Immediate pre-op x-rays are beneficial. The removal can encounter certain difficulties and the surgeon needs to be vigilant & skilful.